Analysis of bioactive compounds and antioxidant capacities in green radish and red radish - Zhang Haoyue; WU Yimei; Xia Xue; Liu Dan; Chen Qing; Zhang Fen; Hou Yanxia; Ma Jie; Tang Haoru; Sun Bo (浙江大学学报. 农业与生命科学版)
Radish (Raphanus sativus), an important original Raphanus vegetable, is widely distributed in China. It exhibits high nutritional value because of rich in vitamins, phenolic compounds, and dietary fiber. Many bioactive compounds show the important biological functions, such as antioxidant and anticarcinogenic effects. Therefore, the colored vegetables, as a rich source of various bioactive compounds, have achieved more and more attentions. Radish can be divided into white radish, green radish and red radish according to skin color. Green and red radishs, which were widely grown in Sichuan Province, could be consumed not only in fresh but also as main raw materials of Sichuan pickles, and the edible parts include the petiole, root peel and root flesh. Although the nutrient qualities in root flesh of radish have been investigated, limited information is available about the bioactive compounds and antioxidant capacities among different edible parts in green radish and red radish.We aimed to investigate the variation of the contents of vitamin C, carotenoids, anthocyanins, proanthocyanidins, chlorophylls, flavonoids, and total phenolics, as well as antioxidant capacities among different edible parts in green radish and red radish. Our systematic study on radish will provide the foundation to guide human consumption.In September 2013, the seeds of green radish (cv. Lutouqing) and red radish (cv. Hongyou) were sown at Ya'an City, Sichuan Province. Petioles and roots were harvested together in early morning, put on ice and transported to laboratory within 10 min. For each sampling, five plants were collected as a replicate, and four independent replicates were taken for analysis. The samples were cleaned and separated according to different edible parts, and then the contents of bioactive compounds and antioxidant capacities were determined. The correlations were analyzed by SPSS 18.0 software.The results showed that both contents of bioactive compounds and antioxidant capacities exhibited remarkable differences among different edible parts in green radish and red radish. In general, the lower contents were found in flesh. The contents of proanthocyanidins, carotenoids and chlorophylls in green radish were notably higher than those in red radish. On the contrary, the contents of vitamin C, anthocyanins and total phenolics in red radish were higher than those in green radish. Moreover, significant positive correlations were found between ferric reducing antioxidant power (FRAP) and all bioactive compounds, respectively, whereas 2,2'-azino-bis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) was just significantly correlated with carotenoids and chlorophylls. The results suggested that FRAP is suitable for the analyses of antioxidant capacity in radish.In conclusion, the contents of bioactive compounds and antioxidant capacities show significant differences among edible parts and species of radish. The edible parts of green radish and red radish contain high nutritional value, and are as good candidate for human daily consumption.